MOOC quality as a challenge for language teaching in digital environments - Amorós Negre, Carla; Recio Diego, Álvaro; Tomé Cornejo, Carmela (Círculo de Lingüística Aplicada a la Comunicación, 2018)
Quality control is one of the great challenges of virtual learning environments. The proliferation of MOOCs (massive open online courses) has shown the need to establish new models for the qualitative evaluation of content and didactic proposals in computer-mediated teaching. The goal of this article is to analyze the concept of quality in these digital environments, especially in language MOOCs (LMOOCs), which have experienced a 250% growth in the last three years despite their format restrictions. To do so, we examine the different quality parameters for MOOC production (student data, non-completion rates, good learning and instructional design, assessment), as well as the main criteria and models suggested to evaluate the quality of MOOCs, such as the MOOC Quality Project (Creelman, Ehlers & Ossiannilsson 2014) or the OpenupEd Quality Label (Rosewell & Jansen 2014), among others. Lastly, we specifically analyze quality applied to language MOOCs in order to suggest a series of proposals of best practices that ensure effective learning.